Wittgensteins begreb om religion - Albinus, Lars (Religionsvidenskabeligt Tidsskrift, 2003)
This article aims at describing Wittgenstein’s notion of religion. The point of departure is taken in his critique of Frazer’s Golden Bough, where magic is described as mistaken science. Wittgenstein’s point is that Frazer’s evolutionistic view of magic and religion is guilty of trivializing the matter. This critique is brought into perspective by Wittgenstein’s general critique of scientific reductionism as a certain language game and his view of magic and religion as forms of life which are simply given for description rather than explanation. In order to appreciate Wittgenstein’s own notion of religion, the article also tries to reconstruct his early notion of God on the grounds of Tractatus and the notebooks, and his later notion of God in relation to his thoughts on ‘language games’, ‘family resemblances’ and ‘forms of life’. Finally, a critical perspective is offered on the relativistic implications in these notions.